2007
DOI: 10.1519/r-19155.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships to Skating Performance in Competitive Hockey Players

Abstract: The purpose of this study was to identify off-ice variables that would correlate to on-ice skating sprint performance and cornering ability. Previous literature has not reported any off-ice testing variables that strongly correlate to on-ice cornering ability in ice hockey players. Thirty-six male hockey players aged 15-22 years (mean +/- SD: 16.3 +/- 1.7 years; weight = 70.8 +/- 10.4 kg; height = 175.6 +/- 4.1 cm) with an average of 10.3 +/- 3.0 years hockey playing experience (most at AA and AAA levels) part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 5 publications
6
65
4
1
Order By: Relevance
“…This indicates that both field-based and laboratory-based assessments can be considered valid tools for coaches when they want to gain knowledge about a female player’s skating abilities. These findings are in agreement with previous studies on male hockey players,14,15,27 which have shown correlations between skating performance and field-based assessments. Farlinger et al14 reported that on-ice cornering and sprint ability were strongly correlated to three hop jump ( r =−0.53, r =−0.78) and broad jump ( r =−0.59, r =−0.74).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that both field-based and laboratory-based assessments can be considered valid tools for coaches when they want to gain knowledge about a female player’s skating abilities. These findings are in agreement with previous studies on male hockey players,14,15,27 which have shown correlations between skating performance and field-based assessments. Farlinger et al14 reported that on-ice cornering and sprint ability were strongly correlated to three hop jump ( r =−0.53, r =−0.78) and broad jump ( r =−0.59, r =−0.74).…”
Section: Discussionsupporting
confidence: 93%
“…Some researchers have indicated that field-based testing is a valid predictor for successful performance in male ice hockey,10,13 while others considered field-based testing as proxies for specific components of hockey performance 14,15. This is a relatively unexplored area in female ice hockey; however, one recent study16 has indicated that field-based assessments can be used to predict speed and recovery ability in lower level (division III) female ice hockey.…”
Section: Introductionmentioning
confidence: 99%
“…Power output is calculated as a mean each 5 s. The best 5 s is called peak power, which is related to maximum and explosive strength abilities of individual [21]. The values can either be expressed in absolute values of peak power (P max ) expressed in Watt (W), relative peak power per body weight (P max .kg −1 ) expressed in Watt per body weight (W.kg −1 ) or relative peak power per FFM expressed in Watt per FFM (W.kg −1 FFM ).…”
Section: Methodsmentioning
confidence: 99%
“…P max is regarded to mirror the alactate anaerobic processes, strength-speed abilities [22] and muscle rheological properties [23] of the tested subject. The WT30 test is a standard laboratory test for ice-hockey players and it is related to their skating performance [21], [24]. The WT30 test was conducted on a calibrated friction loaded cycle ergometer (Monark 894E Peak bike, MONARK, Sweden) interfaced with a microcomputer.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies (2,4,6,8,9,18) have found vertical jump and off-ice 40-yd dash to be significant predictors of on-ice maximum skating speed and acceleration time. However, these studies did not assess performance during actual games or over the course of the season.…”
Section: Discussionmentioning
confidence: 99%